Voor de toegang tot de publieke tribunes van de 2e Kamer op de dag van behandeling worgwetten. Uit: Wereldkroniek, 11-4-1903
Voor de toegang tot de publieke tribunes van de 2e Kamer op de dag van behandeling worgwetten. Uit: Wereldkroniek, 11-4-1903.